(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Diabetes Mellitus is metabolic disorder characterized by hyperglycemia resulting from inadequate insulin secretion, insulin action or both and insulin resistance. Gymnema sylvestre have reported beneficial effect for treating in type 2 diabetes mellitus. Objective: A comparison of the efficacy of homoeopathic medicine gymnema sylvestre 6 CH and gymnema sylvestre mother tincture in the treatment of type 2 diabetes mellitus cases. Material and method: 30 cases of type 2 diabetes mellitus were selected and gymnema sylvestre mother tincture and 6 CH were prescribed for these cases and follow up was every one month, three months and six months. Results: Over a period of 6 months, there was significant reduction in blood sugar levels (fasting and post prandial blood sugar) in both groups. ANOVA repeated measures also showed significant difference P = 0.001. Conclusion: There is significant reduction in fasting blood sugar, post prandial blood sugar levels both groups (gymnema sylvestre 6 CH and gymnema sylvestre homoeopathic mother tincture) in type 2 diabetes mellitus cases. The results suggested that gymnema sylvestre 6 CH and gymnema sylvestre mother tincture has beneficial anti diabetic effective and warrants future investigation.